2023
DOI: 10.3390/antibiotics12121715
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Potentiation as a Promising Strategy to Combat Macrolide Resistance in Bacterial Pathogens

Deepjyoti Paul,
Meenal Chawla,
Taruna Ahrodia
et al.

Abstract: Antibiotics, which hit the market with astounding impact, were once called miracle drugs, as these were considered the ultimate cure for infectious diseases in the mid-20th century. However, today, nearly all bacteria that afflict humankind have become resistant to these wonder drugs once developed to stop them, imperiling the foundation of modern medicine. During the COVID-19 pandemic, there was a surge in macrolide use to treat secondary infections and this persistent use of macrolide antibiotics has provoke… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 100 publications
(109 reference statements)
0
2
0
Order By: Relevance
“…However, with the emergence of drug-resistant bacteria, macrolides have also fallen to the altar. Fortunately, the emergence of antibacterial synergists may save the status of macrolides [55]. In particular, QSIs have the potential to become antibacterial synergists, and combination therapy is likely to become a new means of combating bacterial resistance [56,57].…”
Section: Combination Of Macrolide Antibiotics and Qsismentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the emergence of drug-resistant bacteria, macrolides have also fallen to the altar. Fortunately, the emergence of antibacterial synergists may save the status of macrolides [55]. In particular, QSIs have the potential to become antibacterial synergists, and combination therapy is likely to become a new means of combating bacterial resistance [56,57].…”
Section: Combination Of Macrolide Antibiotics and Qsismentioning
confidence: 99%
“…The synergistic antibacterial potential of the oxazolidinone derivative 30 with MEPM has been previously illustrated. Here, a series of benzoxazolone derivatives were further designed and synthesized, and the synergistic antibacterial effects of multiple compounds (49)(50)(51)(52)(53)(54)(55) with antibiotics were explored. The results showed that the combination of 49-55 (32 µg mL −1 ) with CIP (0.2 µg mL −1 ) or CLA (3.2 µg mL −1 ) significantly increased the mortality of P. aeruginosa PAO1.…”
Section: Combination Of Quinolone Antibiotics and Qsismentioning
confidence: 99%